COMPOSIÇÃO QUÍMICA E FRACIONAMENTO DO ÓLEO ESSENCIAL E OBTIDO DAS FOLHAS DA NECTANDRA LANCEOLATA NESS (LAURACEAE) - COSTA, E. R.; SIMIONATTO, E.; LOURO, G. M.; SANTOS, E. O.; SILVA, V. S.; NICOLAU, C. L. (ANAIS DO ENIC, 2016)
-